On the applicability of semi-empirical methods for calculating the operating processes of a single-stage long-stroke reciprocating compressor in the sphere of wet steam - V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The issues of applicability of well-known semi-empirical methods for calculating the operating processes of low-speed reciprocating compressors for the theoretical study of these processes in the field of wet steam are considered. It is shown that there are significant uncertainty factors in such calculations, suggesting the need to create new semi-empirical calculation methods and the inapplicability of existing ones. The latter is determined by the lack of reliable experimental results, both in terms of the empirical dependencies used to determine the instantaneous heat transfer coefficient in the flow part of a low-speed reciprocating compressor, and in terms of verification of the obtained computational and theoretical results. It is shown that the use of simplifying assumptions such as the absence of leakage through leaks in the working chamber; the constancy of the heat transfer coefficient in the cylinder during the compression process; the equality of the temperature of the cylinder mirror and the boiling point of the working fluid; the calculation of the heat transfer coefficient based on unverified empirical dependencies obtained for other technical facilities, and a number of others are unacceptable, since they lead to unacceptable results. At the same time, given the theoretical attractiveness of the issue under consideration, it can be assumed that in the future a wide range of experimental and theoretical studies of low-speed reciprocating compressors workflows in the field of wet steam, including those aimed at determining empirical dependencies for calculating heat transfer coefficients in the flow part of the low-speed reciprocating compressors stage.